Contextualization of Hadith in Culture and Locality: A Study of the Thoughts of M. Syuhudi Ismail - Dede Miftah; Fatahillah Aly; Dadah (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to examine the contextualization of hadith in relation to culture and locality by highlighting the contributions of classical and modern scholars, including the Indonesian hadith figure, M. Syuhudi Ismail. Through a qualitative approach with library research methods, this study examines classical literature such as the works of Imam Malik, al-Syafi‘ī, al-Ghazālī, al-Syāṭibī, and Ibn Qayyim al-Jawziyyah, as well as contemporary literature from Fazlur Rahman, Amin Abdullah, and M. Syuhudi Ismail. The analysis is conducted descriptively and analytically to trace the relationship between the hadith text, the socio-cultural context, and the maqāṣid al-syarī‘ah. The results show that the contextualization of hadith is a scientific effort to maintain the relevance of the prophetic message amidst the dynamics of diverse societies and cultures. In M. Syuhudi Ismail's view, the understanding of hadith cannot be separated from the elements of space, time, and culture. He proposed a distinction between universal, temporal, and local values ​​in hadith and emphasized the importance of a balance between the authenticity of the sanad and the validity of understanding (ṣaḥīḥ al-fahm). His idea asserted that hadith must be understood through an integration of textual, historical, and cultural approaches so that its teachings remain a living tradition in society. This research asserts that the contextualization of hadith is a continuity between the turāth tradition and modern methodological renewal, where culture and locality become media to actualize the universal values ​​of the sunnah in the reality of humanity.